2023
DOI: 10.3390/medicina59020395
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Postinduction Blood Glucose on Intraoperative Hypothermia

Abstract: Background and Objectives: Hypothermia frequently occurs in patients undergoing surgery and is associated with adverse complications. Therefore, this study aimed to investigate the postinduction blood glucose and occurrence of intraoperative hypothermia in patients undergoing laparoscopic surgery. Materials and Methods: This retrospective observational study included 334 patients aged ≥20 years who had undergone elective laparoscopic surgery. The primary outcome of this study was the incidence of intraoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In this study, underlying disease refers to concomitant diseases related to thermogenesis, such as having brain disease, thyroid disease, hypertension, diabetes, etc, and these patients have a higher incidence of hypothermia. Studies have found that if the blood glucose after induction is out of range, it will affect the occurrence of hypothermia in diabetic patients [ 27 ]. But the underlying disease was not included as a risk factor in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, underlying disease refers to concomitant diseases related to thermogenesis, such as having brain disease, thyroid disease, hypertension, diabetes, etc, and these patients have a higher incidence of hypothermia. Studies have found that if the blood glucose after induction is out of range, it will affect the occurrence of hypothermia in diabetic patients [ 27 ]. But the underlying disease was not included as a risk factor in this study.…”
Section: Discussionmentioning
confidence: 99%